Pan-cancer analysis of CHRDL1 expression and its mechanistic role in inhibiting EMT via the TGF-β pathway in lung adenocarcinoma - Dong, Honghong; Tian, Yahui; Xin, Shaowei; Guo, Yujie; Jiang, Suxin; Wan, Zitong; Wang, Huaiyu; Han, Yong (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe primary objective of this study is to conduct a pan-cancer analysis of CHRDL1 expression, to determine its correlation with patient survival rates, immune cell infiltration, and drug sensitivity. Additionally, the study aimed to further validate the mechanistic role of CHRDL1 in lung adenocarcinoma (LUAD), clarifying its contribution to tumorigenesis and evaluating its potential as a therapeutic target for LUAD.MethodsWe employed bioinformatics strategies to analyze CHRDL1 expression using data from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression Project (GTEx). Survival analysis was executed with GEPIA2, while drug sensitivity to chemotherapeutic agents was evaluated via the CellMiner database. Mutational profiles were examined using cBioPortal, and the immune microenvironment was assessed through the TIMER database. To substantiate our findings, we conducted in vitro cellular assays and in vivo animal models to validate the mechanistic actions of CHRDL1 in LUAD.ResultsCHRDL1 expression levels showed significant variation across different cancer types, with tumor tissues typically demonstrating lower expression compared to their normal counterparts. In certain cancers, elevated CHRDL1 expression was linked to poorer survival outcomes, whereas in LUAD, it was associated with improved survival. Furthermore, CHRDL1 expression correlated with the IC50 values of multiple chemotherapeutic drugs and played a role in modulating the immune microenvironment. We discovered that CHRDL1 inhibits the epithelial-mesenchymal transition (EMT) in LUAD through the TGF-β pathway.ConclusionCHRDL1 exerts a complex influence on cancer development and progression, particularly in LUAD, by impacting tumor progression, immune regulation, chemosensitivity, and EMT regulation. This research offers valuable insights into the overarching mechanisms of cancer progression and aids in the discovery of innovative therapeutic strategies for LUAD treatment.